(untitled) (Fiep Bulletin - online, 2020)
The objective of the research was to determine the relationship between academic activities in the institutional platform (Moodle), and the perception of the teaching-learning process, by students of the Sports and Physical Culture program of the Autonomous University of Caribbean in the year 2018; The focus of this research was Quantitative, with a descriptive study and a descriptive transactional design, the population employed were 40 students of the sixth and seventh semester of the Sports and Physical Culture program of the Autonomous University of the Caribbean in 2018, allowing to know the relationship that exists between the virtual platform and the perception that the students of the Sports and Physical Culture program possess of the teaching - learning process, carrying out the virtual activities established by their teachers. Among the results, it was found that the majority of the students of the Sports and Physical Culture program, agreed that the virtual academic activities established in the Moodle platform called by the Autonomous University of the Caribbean as EXIA, allowed students to generate an active role in its formation process; On the other hand, the students perceived that the activities promoted the elaboration of research projects.